Efficacy of omalizumab in the management of moderate-to-severe asthma in paediatric patients: a clinical evaluation - Yamini, Chukka; Malisetty, Harshini; Vidyadhari, Sriramoju; Kudikala, Naveen; Kathuroju, Sindhuja; Ammika, Rishika (International Journal of Research in Medical Sciences, 2026)
Background: Children diagnosed to have mild-to-intense allergic asthma (AA) often present with comorbid chronic sinusitis (CS), which complicates the management of their condition and adversely affects their quality of life (QoL). Omalizumab (OM), a monoclonal antibody (MCA) targeting IgE, has demonstrated potential in the management of both conditions; however, the availability of real-world data in pediatric populations is still restricted. Methods: This study involved children having mild-to-intense AA and chronic rhinosinusitis, recruited from the Pediatric Allergy and Pulmonology Clinic at Indira Gandhi Institute of Child Health, Bengaluru, India. Omalizumab was administered from January 2021 to May 2023, subcutaneously every 2-4 weeks at doses of 150-600 mg based on body mass index and baseline IgE levels. Asthma control was gauged using the Childhood Asthma Control Test (C-ACT), Asthma Control Test (ACT), fractional exhaled nitric oxide (FeNO), and lung function (LF) indices. Results: Omalizumab treatment significantly improved asthma control, shown by increased C-ACT/ACT scores (p<0.05) and a notable drop in FeNO levels (p<0.05). LF indices associated with small airway function (PEF%pred, FEF75%, FEF50%, FEF25–75%) demonstrated noteworthy improvement (p<0.05), whereas changes in FEV1%pred and FEV1/FVC were not statistically significant. VAS scores for CS symptoms significantly decreased (p<0.05). Conclusions: Omalizumab effectively treats children having mild-to-intense AA and CS, enhancing asthma control, small airway function, and alleviating sinusitis symptoms. These findings endorse omalizumab as an additional therapy for this difficult pediatric group.